Cross-Metathesis of Methallyl Halides: Concise Enantioselective Formal Total Synthesis of (–)-Presphaerene - Mandava, Suresh; Koo, Jaun; Hwang, Jungjoong; Nallapaneni, Hari Krishna; Park, Haeil; Lee, Jongkook (Frontiers in Chemistry, 2020)
The cross-metathesis (CM) of methallyl halides catalyzed using four different ruthenium-based complexes—Grubbs catalyst, Grubbs second-generation catalyst, Hoveyda-Grubbs second-generation catalyst, and Stewart-Grubbs catalyst—was investigated. When methallyl chloride or bromide was reacted with a model substrate containing a benzyl ether group, the Grubbs catalyst and Grubbs second-generation catalyst did not promote the reaction well. However, the Hoveyda-Grubbs second-generation catalyst and Stewart-Grubbs catalyst afforded the corresponding products in moderate to good yield with moderate E/Z selectivity. Accordingly, several functionalized methallyl halides were prepared by CM. Various functional groups were well tolerated in this system when the Stewart-Grubbs catalyst was used. To demonstrate the practical utility of our method, methallyl halide CM was successfully employed for the formal total synthesis of a natural product, (–)-presphaerene, in which the precursor of the key cyclopentanecarboxylate intermediate was efficiently prepared in three steps.